1985
DOI: 10.1038/clpt.1985.41
|View full text |Cite
|
Sign up to set email alerts
|

Metoclopramide kinetics in patients with impaired renal function and clearance by hemodialysis

Abstract: Metoclopramide kinetics were examined in 24 adult patients with diminished renal function and in eight healthy subjects with normal renal function. Creatinine clearance correlated with metoclopramide plasma clearance, renal clearance, nonrenal clearance, and elimination t1/2. Regardless of renal function, renal clearance accounted for less than or equal to 21% of total plasma clearance. Nonrenal clearance was reduced in patients and accounted for most of the reduction in plasma clearance. The comparatively sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…For instance, the metabolism of zidovudine and metoclopramide, which is primarily mediated by glucuronidation, is reduced in patients with renal failure. 20,31,32 Acetylation also seems to be reduced in patients with CRF; several reports have demonstrated that the metabolic clearance of procainamide is reduced by approximately 60% in renal failure. 2,23,24 Moreover, a decrease in the acetylation of isoniazid has been reported in patients with CRF.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the metabolism of zidovudine and metoclopramide, which is primarily mediated by glucuronidation, is reduced in patients with renal failure. 20,31,32 Acetylation also seems to be reduced in patients with CRF; several reports have demonstrated that the metabolic clearance of procainamide is reduced by approximately 60% in renal failure. 2,23,24 Moreover, a decrease in the acetylation of isoniazid has been reported in patients with CRF.…”
Section: Discussionmentioning
confidence: 99%
“…Sulfisoxazole is acetylated, glucuronidated, and metabolized partially by CYP2C9. A summary of clinical data showing significant alterations in nonrenal clearance in CRF for a number of drugs is shown in (Table 2) [7,[51][52][53][54][55][56][57][58][59][60][61]. The majority of these studies involve ESRD patients.…”
Section: Clinical Investigations: Effect Of Chronic Renal Failure On mentioning
confidence: 99%
“…This would be expected from the large volume of distribution of this drug. Therefore, our results and those of Lehmann et al (1985) suggest that dosage supplementation subsequent to dialysis is unnecessary.…”
Section: Discussionmentioning
confidence: 80%
“…Although previous investigators (Bateman et al, 1981;Lehmann et al, 1985) have examined the basic pharmacokinetics and removal of drug by haemodialysis, the present investigations focussed on a somewhat different aspect of metoclopramide pharmacokinetics in renal failure. When a patient is haemodialysed, the blood is 'cleansed' of end-products of metabolism many of which could be potential inhibitors of drug metabolism (Terao & Shen, 1985).…”
Section: Discussionmentioning
confidence: 99%